Claudin-8d is a cortisol-responsive barrier protein in the gill epithelium of trout. (October 2017) - Kolosov, Dennis; Kelly, Scott P
Abstract : The influence of claudin (Cldn) 8 tight junction (TJ) proteins on cortisol-mediated alterations in gill epithelium permeability was examined using a primary cultured trout gill epithelium model. Genes encoding three Cldn-8 proteins ( cldn-8b, -8c and -8d ) have been identified in trout and all are expressed in the model gill epithelium. Cortisol treatment 'tightened' the gill epithelium, as indicated by increased transepithelial resistance (TER) and reduced paracellular [ 3 H]polyethylene glycol (MW 400 Da; PEG-400) flux. This occurred in association with elevated cldn-8d mRNA abundance, but no alterations in cldn-8b and -8c mRNA abundance were observed. Transcriptional knockdown (KD) of cldn-8d inhibited a cortisol-induced increase in Cldn-8d abundance and reduced the 'epithelium tightening' effect of cortisol in association with increased paracellular PEG-400 flux. Under simulated in vivo conditions (i.e. apical freshwater), cldn-8d KD hindered a cortisol-mediated reduction in basolateral to apical Na + and Cl − flux (i.e. reduced the ability of cortisol to mitigate ion loss). However, cldn-8d KD did not abolish the tightening effect of cortisol on the gill epithelium. This is likely due, in part, to the effect of cortisol on genes encoding other TJ proteins, which in some cases appeared to exhibit a compensatory response. Data support the idea that Cldn-8d is a barrier protein of the gill epithelium TJ that contributes significantly to corticosteroid-mediated alterations in gill epithelium permeability.